Mechanisms of disseminated cancer cell dormancy: an awakening field - Sosa, María Soledad; Bragado, Paloma; Aguirre-Ghiso, Julio A. (Nature reviews. Cancer, 2014)
Key Points It is thought that dormant disseminated tumour cells (DTCs) are the cellular entity responsible for clinical dormancy and subsequent metastasis after surgery and adjuvant treatment. Cellular dormancy is regulated by intrinsic and autocrine signals, as well as signals derived from immune and endothelial cells. Stress signalling pathways activated by exogenous stressors, intrinsic damage or microenvironmental cues can trigger dormancy. The balance between ERK and p38 signalling regulates dormancy versus proliferation decisions in different cancer models. Autophagy is important for the induction of dormancy and cell survival. Morphogenetic cues and intrinsic pathways that regulate cell quiescence and pluripotency or 'stemness' might also coordinate DTC dormancy. Mechanisms that were thought to regulate tumour mass dormancy, such as cytotoxic CD8 + T cells or non-angiogenic endothelial cells, may in fact regulate cellular dormancy. Pathways and mechanisms regulating cellular dormancy can be manipulated to induce dormancy. Dormancy models have identified gene signatures that are predictive of delayed onset of metastasis in patients and have provided a first shortlist of genes that may serve as dormancy markers to test in DTCs. Disseminated tumour cells that survive treatment may become dormant and their 'awakening' may be the source of metastases. This Review discusses the mechanisms and factors that regulate tumour dormancy, including the extracellular and stromal microenvironments, autophagy and epigenetics. The authors also discuss how this information could be used therapeutically for metastatic disease. Metastases arise from residual disseminated tumour cells (DTCs). This can happen years after primary tumour treatment because residual tumour cells can enter dormancy and evade therapies. As the biology of minimal residual disease seems to diverge from that of proliferative lesions, understanding the underpinnings of this new cancer biology is key to prevent metastasis. Analysis of approximately 7 years of literature reveals a growing focus on tumour and normal stem cell quiescence, extracellular and stromal microenvironments, autophagy and epigenetics as mechanisms that dictate tumour cell dormancy. In this Review, we attempt to integrate this information and highlight both the weaknesses and the strengths in the field to provide a framework to understand and target this crucial step in cancer progression.